2017
DOI: 10.1007/s12053-017-9577-5
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency in the food retail sector: barriers, drivers and acceptable policies

Abstract: The objective of this research is to empirically examine the drivers and barriers to energy efficiency measures in an important energy-using sector, namely the food retail sector, and support more effective energy efficiency policies for this sector. Although food retailers consume a significant amount of energy due to the refrigeration, air conditioning and specialised lighting needs of stores, there has been little research in this sector on the barriers and drivers for implementing energy efficiency measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Relating this to the Cooremans decision-making model shows that the major focus of the reviewed studies was found in the later part of the decision-making process, namely the choice step. Many of the findings in the studies of barriers to energy efficiency (e.g., [25,39,40,46,48]) are in line with the previous findings from Brunke et al [4], saying that the most important perceived barriers are related to the economic category in the taxonomy from Cagno et al [5].…”
Section: Concluding Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Relating this to the Cooremans decision-making model shows that the major focus of the reviewed studies was found in the later part of the decision-making process, namely the choice step. Many of the findings in the studies of barriers to energy efficiency (e.g., [25,39,40,46,48]) are in line with the previous findings from Brunke et al [4], saying that the most important perceived barriers are related to the economic category in the taxonomy from Cagno et al [5].…”
Section: Concluding Discussionsupporting
confidence: 81%
“…External drivers (e.g., technical support, clarity and trustworthiness of information) play an important role in the middle part of the decision-making process while in the final steps internal drivers (e.g., staff with real ambitions, information about real costs, cost reduction from lower energy) seem to be of more relevance. In a survey of 42 small food retailers the barriers to and drivers for energy efficiency measures were examined together with the acceptability of energy efficiency policies [48]. Of the five top-ranked barriers, four were related to economic barriers where too high initial cost of equipment and lack of internal finances were ranked equally high.…”
Section: Barriers and Driversmentioning
confidence: 99%
“…Apeaning and Thollander ranked the barriers to improved energy efficiency in one of Ghana's largest industrial areas [52]. Dixon et al ranked the barriers to energy efficiency in the food retail sector [53]. Backman identified barriers to energy efficiency in the Swedish non-energy intensive SMEs [22].…”
Section: Barriersmentioning
confidence: 99%
“…In one of Ghana's largest industrial areas, Apeaning and Thollander ranked the driving forces of improved energy efficiency [52]. Dixon et al found the main drivers for energy efficiency, in the food retail sector, to be reduced energy cost, energy efficiency subsidies, future energy costs, cheap energy efficiency equipment, energy efficiency information, energy supplier, green image, examples, competitive advantage, free energy audit, and head office requirement [53]. In a review of empirical drivers to energy efficiency among manufacturing firms, it was found that the main drivers were of organizational and economic nature where management and operating costs played an important role [66].…”
Section: Driversmentioning
confidence: 99%
“…Likewise, Sullivan & Gouldson (2013 examined retail corporate action on climate change, regarding the period 2000-2010, as well as the rates of improvement in English and American retailers' energy consumption and GHG emissions. Other studies assessed energy and carbon efficiency in retail buildings (Dixon-O'Mara and Ryan, 2018) (Christina et al, 2015;Ji et al, 2017;Lukić et al, 2018;Bălan, 2010) and studied policy and strategy challenges to address climate change regarding the building stock (Sebi et al, 2019;Carballo-Penela and Castromán-Diz, 2015).…”
Section: Introductionmentioning
confidence: 99%